PENDEKATAN HERMENEUTIKA AL-QURAN KONTEMPORER NASHR HAMID ABU ZAID - Ahmad Zayyadi (MAGHZA, 2017)
The controversial thoughts of Nasr Hamid Abu Zayd provide enough variation and inspiration for the development of religious thought, especially regarding the hermeneutical theory applied in the gender discourse and women discussed in this article. In general, his hermeneutical theory of Abu Zayd is more critical of the study of the Qur'an as a "productive hermeneutics" reading in the words of hans George Gadamer, and al-qira'ah al-muntijah according to Nasr Hamid Abu Zayd. This reading model is a new way of reading the Qur'an productively. the author uses hermeneutics through the primary texts in Islamic law especially the Qur'an and sunnah. this humanist-critical- earning reading method has in part inspired some Muslim scholars to interpret the Qur'an, such as Fazlur Rahman, Mohammed Arkoun, Hassan Hanafi, and Farid Essack. Nevertheless, Abu Zayd deepens his humanistic hermeneutics by providing an interpretation that can reveal the side of justice in a text mainly related to discriminatory texts against women, justice, democracy, and human rights. Abu Zayd's hermeneutical theory was then applied to gender and women's issues through the interpretive theories of al-Qur'an and Sunna texts as a contribution to contemporary Islamic legal thought.